A New Approach for Increasing the Chelating Capacity of the Tartrate Ion in the Extraction of Copper from Ores - Hidalgo Apaza, Angie Arlette (2024)
The role of the tartrate ion in the extraction of copper from oxidized ore in aqueous alkaline medium is first reported. This was demonstrated by a sequential evaluation of the following: (i) The formation of an ionic complex resulting from the interaction of copper salts (CuSO4, Cu(NO3)2) with an alkaline aqueous solution of tartrate ions. (ii) The treatment of metallic copper with hydrogen peroxide. (iii) Spectrophotometric and potentiometric studies of malaquite. These studies demonstrated that the Cu(II)–tartrate interaction is only possible due to the chelating activity of tartrate ion leading to the formation of the [Cu(OH)2C4H4O6] 2− anion complex and the lixiviation of the oxidized mineral is controlled by the chelating agent. The advantage of this approach relative to previous ones is discussed. Final conclusions are given.